Rekonstruksi hukum kewarisan anak dari perkawinan sirri di pengadilan agama - Supriyadi Supriyadi (State Institute of Islamic Studies (IAIN) Salatiga, 2016)
Children born out of marriage Sirri has a different position with children from other marriages. Son of marriage Sirri, in the perspective of religion is legitimate, but legally is not recorded in the Office of Religious Affairs. The existence of child in the marriage Sirri must get legal certainty and the protection of law. Decision of the Constitutional Court (MK) has provided certainty and legal protection, but in a religious court the verdict has not been granted a constitutional manner. Therefore it is necessary to reconstruct the inheritance law of children born out of marriage Sirri by incorporating Court decision No. 46 / PUU-VIII / 2010 as a source of law in the legal system of inheritance in religious courts. Law should provide protection and legal certainty to the status of a child born out of marriage Sirri and rights available to him, although the validity of the marriage is still in question.